ANALISIS USAHA CAP TIKUS DI DESA POOPO KECAMATAN PASSI TIMUR KABUPATEN BOLAANG MONGONDOW - Natalia F. Tambayong; O. Esry H. Laoh; Oktavianus ., Porajouw (AGRI-SOSIOEKONOMI, 2016)
This study aimed to analyze the business of â€œCap Tikusâ€ in Poopo Village, District of Eastern Passi of Bolaang Mongondow Regency. This study was conducted over two months, from February to March 2016. The population of â€œcap tikusâ€ farmers in Poopo village many as 44 people. Of the total population taken samples as many as 24 people (54%) by using purposive sampling method. The data used in this study are primary data and secondary data. Primary data was obtained by conducting a live interview on farmers by using a list of questions that had been prepared. Secondary data were obtained from the agencies involved in this study of The data analysis used in this study is bussiness income analysis. These results indicate that the production process of â€œcap tikusâ€ in Poopo Village District of Eastern Passi performed by farmers themselves from the preliminary stage to the manufacturing stage. Raw materials of sugar palm (nira or saguer), firewood and bamboo are materials owned by the farmers themselves (not bought). Business of â€œcap tikusâ€ is very helpful to the people in the Poopo Village because of this effort farmers can build houses, send children to school, and can meet the needs of daily consumption. Therefore, this business of â€œcap tikusâ€ is used as the principal livelihood by the people in the Poopo Village District of Eastern Passi of Bolaang Mongondow Regency. *er*